ANALYSIS OF ASSERTIVE SPEECH ACTS ON KICK ANDY TALK SHOW PROGRAM IN ‘SAVE THE INDONESIAN CHILDREN’ EDITION - Yanti Suryanti; Cintya Nurika Irma (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: This study intends to describe the assertive speech acts on Kick Andy Talk Show program in ‘Save the Indonesian children’ edition. It is a descriptive qualitative study. The data was collected from the speech containing assertive speech act on the conversation. The method of this research was simak (listening) method. The technique of data collection was documentation in form of video recording, simak bebas cakap (listening without speaking), and catat (field note). Triangulation was used to validate the data. The steps in analyzing the data were data reduction, data display, and conclusion making. The result revealed that there were 56 stating assertive speech acts, 4 complaining assertive speech acts, 4 suggesting assertive speech acts, and no claiming nor bragging assertive speech acts. Keywords: Assertive speech acts, pragmatics, Kick Andy Talk Show Abstrak: Penelitian ini bermaksud untuk mendeskripsikan tindak tutur tegas pada program Kick Andy Talk Show di edisi 'Save the Indonesian Children'. Ini adalah penelitian kualitatif deskriptif. Data dikumpulkan dari pidato yang berisi tindak tutur tegas pada percakapan. Metode penelitian ini adalah metode simak (menyimak). Teknik pengumpulan data adalah dokumentasi dalam bentuk rekaman video, simak bebas cakap, dan catat (catatan lapangan). Triangulasi digunakan untuk memvalidasi data. Langkah-langkah dalam menganalisis data adalah reduksi data, tampilan data, dan pengambilan kesimpulan. Hasil penelitian menunjukkan bahwa ada 56 menyatakan tindak tutur tegas, 4 mengeluh tindak tutur tegas, 4 menyarankan tindak tutur tegas, dan tidak mengklaim atau menyombongkan tindak tutur tegas. Kata kunci: Tindak tutur asertif, pragmatik, Kick Andy Talk Show